2014
DOI: 10.1590/s1984-82502011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline: production, waste treatment and environmental impact assessment

Abstract: The frequent occurrence of pharmaceuticals in the aquatic environment requires an assessment of their environmental impact and their negative effects in humans. Among the drugs with high harmful potential to the environment are the antibiotics that reach the environment not only, as may be expected, through the effluents from chemical and pharmaceutical industries, but mainly through the sewage and livestock; because around 25 to 75% of the ingested drugs are excreted in unchanged form after the passage throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(80 citation statements)
references
References 54 publications
0
64
0
11
Order By: Relevance
“…; Borghi & Palma ). Photodegradation can occur by two main ways: directly (absorption of radiation by the compound) and indirectly (photosensitization by natural water constituents, such as DOM) (Borghi & Palma ). However, it is worth to notice that DOM can also have a filter effect, as it absorbs solar light, causing an inhibition of contaminant photodegradation.…”
Section: Environmental Fatementioning
confidence: 99%
See 2 more Smart Citations
“…; Borghi & Palma ). Photodegradation can occur by two main ways: directly (absorption of radiation by the compound) and indirectly (photosensitization by natural water constituents, such as DOM) (Borghi & Palma ). However, it is worth to notice that DOM can also have a filter effect, as it absorbs solar light, causing an inhibition of contaminant photodegradation.…”
Section: Environmental Fatementioning
confidence: 99%
“…). In fact, solar photodegradation can be affected by several factors, namely pH, composition and turbidity of water, season, latitude and own absorption spectrum of the compound (Kummerer ; Borghi & Palma ).…”
Section: Environmental Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Por ello, grandes cantidades de estos fármacos son liberados en aguas residuales municipales por excreción o eliminación (Lien et al 2016), y se han detectado en diferentes ambientes acuáticos como ríos (Zhang et al 2015), agua para acuacultura (Pham et al 2015), influentes y efluentes de plantas de tratamiento de aguas residuales (Rodríguez-Mozaz et al 2015) y principalmente en los efluentes de hospitales (CastroPastrana et al 2015). Por otro lado, se encontró una alta incidencia de cepas de Salmonella resistentes a tetraciclina, lo que podría estar relacionado con el amplio uso de este antibiótico para tratamiento humano, así como en actividades agrícolas y pecuarias (Borghi y Palma 2014). Además, se ha reportado que más del 70 % de este antibiótico es excretado después de la medicación, y que su alta hidrofobicidad y baja volatilidad, le permiten prevalecer por periodos prolongados en ambientes acuáticos (Daghrir y Drogui 2013).…”
Section: Cuadro III Patrones De Resistencia a Antibióticos De Los Seunclassified
“…In the case of indirect degradation, strong oxidizing radicals are generated by natural components and these radicals react with drug molecules. 42 Jiao et al indicated that the positively charged tetracycline (TC + ) form of TC molecules substantially inhibited photolysis and, contrary to this, the TC 0 form encouraged photolysis. 43 Protonation states of the TC give information about the stability of the structure in media with different pH values.…”
Section: Scheme 2 Keto-enol Tautomerism Of Doxmentioning
confidence: 99%